The diagnostic value of ultrasound in pediatric testicular torsion with preserved flow - Xu, Zhihua; Wu, Junbo; Ni, Shuangshuang; Luo, Hongxia (Frontiers in Pediatrics, 2022)
Background: Testicular torsion is the reduction of blood flow to the testis after spermatic cord torsion. For patients the diagnosis of testicular torsion is controversial and complicated by the fact that ultrasound blood flow signals are not significantly reduced in comparison to the unaffected, healthy, testis, despite persistent symptoms on the affected side. Our study’s aim is to investigate the diagnostic characteristics of high-resolution ultrasonography in pediatric testicular torsion with preserved flow, so as to increase diagnostic accuracy. Methods: Seven pediatric patients aged 49 days to 15 years old, with preserved blood flowl, but surgically diagnosed as testicular torsion, from October 2017 to August 2019, were retrospectively included in the study. The imaging manifestations of high-frequency ultrasonography, were evaluated. Results: All cases had preserved testicular blood flow, but the surgical findings showed various degrees of twist, from 90° to 540°. Preoperative ultrasound showed spermatic cord distortion in all cases, and testicular long axis tilting in four cases(4/7=57.1%). Conclusion: In some testicular torsion cases, Color Doppler may show normal or increased blood flow signals in the testis. We should further observe the morphology and position of the testes and epididymides, the echo of the testicular parenchyma, and, especially evaluate the "whirlpool sign" in the spermatic cord, so as to avoid missing testicular torsion with blood flow signals.